Integrated IP - Comellas, J.
Future transport networks will have to cope with the continuous growth of IP traffic. Furthermore, transport networks need to evolve so as to drastically reduce both deployment costs and operating expenses. A reasonable strategy to achieve this goal consists of simplifying the network architecture by reducing the number of layers. Assuming a peer model IP over optical network, we propose an integrated routing strategy that takes into account constraints and dynamic occupancy of both the IP and optical layers. The collaboration of both layers in the routing process leads to optimization of network performance. The main emphasis is on the implementation requirements of this grooming functionality using GMPLS-TE mechanisms. Simulation results show the benefits obtained by applying this strategy.
Keywords: GMPLS; GMPLS-TE mechanisms; IP over optical network; IP traffic; Constraints; Deployment costs; Dynamic occupancy; Future transport networks; Integrated IP/WDM routing; Network architecture; Network performance optimization; Operating expenses; Optical networks; Peer model; Transport networks